1991
DOI: 10.1104/pp.96.3.744
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Spearmint Mutant That Resembles Peppermint in Monoterpene Content

Abstract: A radiation-induced mutant of Scotch spearmint (Mentha x graclis) was shown to produce an essential oil containing principally C3-oxygenated p-menthane monoterpenes that are typical of peppermint, instead of the CS-oxygenated monoterpene family characteristic of spearmint. In vitro measurement of all of the enzymes responsible for the production of both the C3-oxygenated and CS-oxygenated families of monoterpenes from the common precursor (-)-limonene indicated that a virtually identical complement of enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…In spite of the significant differences in essential oil chemistry, the observation that both dehydrogenases of peppermint and spearmint appear to utilize (2)-trans-carveol and (2)-trans-isopiperitenol as substrates (Croteau et al, 1991), and the facts that spearmint is a parent of peppermint (Murray et al, 1972;Harley and Brighton, 1977) and that other genes of the two species are very similar (Lupien et al, 1999), suggested that the target monoterpenol dehydrogenases would also be very similar. Polyclonal antibodies prepared against the peppermint ISPD ( Turner and Croteau, 2004) were used for immunoblotting of secretory cell extracts.…”
Section: Immunodetection Of Carveol Dehydrogenasementioning
confidence: 99%
See 3 more Smart Citations
“…In spite of the significant differences in essential oil chemistry, the observation that both dehydrogenases of peppermint and spearmint appear to utilize (2)-trans-carveol and (2)-trans-isopiperitenol as substrates (Croteau et al, 1991), and the facts that spearmint is a parent of peppermint (Murray et al, 1972;Harley and Brighton, 1977) and that other genes of the two species are very similar (Lupien et al, 1999), suggested that the target monoterpenol dehydrogenases would also be very similar. Polyclonal antibodies prepared against the peppermint ISPD ( Turner and Croteau, 2004) were used for immunoblotting of secretory cell extracts.…”
Section: Immunodetection Of Carveol Dehydrogenasementioning
confidence: 99%
“…(2)-Carveol was used as substrate in the initial screen, because it is more readily available than (2)-trans-isopiperitenol. Based on previous results (Croteau et al, 1991) …”
Section: Isolation Of a Cdna Encoding Isopiperitenol Dehydrogenasementioning
confidence: 99%
See 2 more Smart Citations
“…The major component, pulegone, was isolated by silica gel chromatography and determined to be the l-enantiomer based on its optical rotation. Since l-pulegone is supposed to be biosynthesized via d-limonene, 20) A. rugosa containing ubiquitous l-pulegone was expected to be a good source for cloning the d-limonene synthase gene. Using cDNA from A. rugosa as a template, a core fragment containing the 3Ј-flanking region of limonene synthase gene was obtained by PCR amplification with sense primer A, and subsequent 5Ј-RACE gave the 5Ј-terminal sequence.…”
Section: Resultsmentioning
confidence: 99%